Elipse de Steiner - Santana, Gleisson Rodrigues (2014)
This work is focused on demonstrating, using geometric tools, the Steiner's Ellipse theorem which says that all ellipses entered in a given triangle, the larger area is touching the triangle sides in their respective middle points. For this we did, in chapter one, an approach to the study of triangles, the ellipses, the orthogonal projection, and we present some results of arithmetic and geometry, this work titled as preliminary lemmas, to be the tools (prerequisites) for proof the theorem that the main is made in chapter two. We conclude by presenting, in chapter three, some applications and some scripts for lessons in how to use the ellipse, and in particular Steiner's Ellipse, day-to-day and in the classroom.